Strategi Pembelajaran Berbasis Nilai-Nilai Kearifan Lokal dalam PKn di Sekolah Dasar - Herliyanto, Muci (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
his study aims to analyze learning strategies based on local wisdom values in Civic Education (PKn) at the elementary school level as an effort to strengthen students’ character and cultural identity. This research employed a library research method with subjects including theories and concepts related to character education and culture-based learning, and the objects consisting of scientific documents, academic journals, and reference books published within the last five years. Data collection techniques involved documentation and literature review, while data analysis used a descriptive-analytical approach. The results indicate that implementing learning strategies integrating local wisdom values such as mutual cooperation, tolerance, and deliberation enhances students’ understanding of national values, fosters mutual respect, and nurtures love for local culture. The study concludes that learning strategies based on local wisdom values are highly relevant and effective for Civic Education in shaping students' character from an early age.